Central European Functional Programming School : 5th Summer School, CEFP 2013, Cluj-Napoca, Romania, July 8-20, 2013, Revised selected papers /: 5th Summer School, CEFP 2013, Cluj-Napoca, Romania, July 8-20, 2013, Revised selected papers. (2015) - Unknown
No abstract available